Photonic Horn Jets and Whispering Gallery Modes in Dielectric Micro-Cylinders With Two Point-Source Illumination - Shadi A. Alboon; Qing Huo Liu; Ibrahim Mahariq (IEEE Photonics Journal)
The interaction of light with micro-scale dielectric structures has garnered significant attention in recent years due to its potential applications in various fields ranging from photonics to biomedical imaging. In this context, this study investigates the generation of twin photonic jets from a dielectric micro-cylinder illuminated by two point-sources. The effect of different parameters on the jet's shape profile and length was analyzed. Those parameters include the cylinder's refractive index and radius, the source distance from the cylinder, and the vertical displacement between the sources. Innovatively, this study introduces the concept of ‘Horn Jets' to characterize the twin photonic jets resulting from the illuminated dielectric micro-cylinder, marking a significant conceptual advancement in the field. Moreover, the generation of whispering gallery modes (WGMs) is investigated. The outcomes obtained through the spectral element method highlight the possibility of generating WGMs by meticulously selecting the cylinder's radius and refractive index, under the scenario of two-point-source illuminations. The results show that the magnitude of the WGMs resonance significantly lies on the vertical displacement due to the resulting interference pattern's dark and bright fringes with the cylinder edges.